Justification of consumer market segmentation as a mandatory tool of strategic marketing - Rozhko, Viktor (Technology audit and production reserves, 2023)
The object of research is the theoretical aspects of consumer market segmentation and its role in strategic marketing. Ukrainian enterprises try to use and carry out various measures to increase the competitiveness of products, actively using methods of internal planning and management based on the principles of strategic marketing. One of the tools for developing a marketing plan in strategic marketing is segmentation. However, the content of strategic marketing is debatable; there is no unambiguous comprehensive approach, according to which consumer market segmentation is carried out. Thus, the development of methodological principles of segmentation of the consumer market, as a mandatory tool of strategic marketing, is an objective and urgent necessity. This determines the topic of this study. The work highlights the features of segmentation of the consumer market. It is emphasized that in modern conditions the segmentation of the consumer market is a mandatory tool of strategic marketing. The principles that must be used in order to segment the consumer market are proposed. Researched that segmentation of the consumer market should be carried out according to the following characteristics: geographical, industry, functional purpose of products, importance of consumers, forms of ownership. Stages of segmentation of the enterprise's consumer market have been developed. A number of measures in strategic marketing are proposed, which will allow a comprehensive approach to the development of the company's marketing plan, namely: development of a drink different from those presented on the market; development of an effective advertising campaign, which will be directed to a certain group of consumers; it is recommended to pay special attention to the development of the product name.